Effects of lesson study on science teacher candidates teaching efficacies - Murat, Pektas (Academic Journals, 2014)
The aim of this study was to investigate the effects of the lesson study process on science teacher candidates’ teaching in terms of lesson plan content, pedagogy and classroom management based on expert, peer and self-evaluations. The participants of this case study consisted of 16 teacher candidates in elementary science education in their fourth year of school. Participants conducted a three-phase lesson presentation, and each phase was observed and commented on by experts, peers and the lecturers.  All evaluations indicated positive changes in terms of lesson planning and design, creating a positive learning environment, engaging students with meaningful content, and assessing student learning.   Keywords: case study,lesson study, science education, teacher education.
Keywords: 4. Education; 10. No inequality; 16. Peace & justice; 7. Clean energy